(untitled) - Kerin, Roger A. (Boston, 2011)
Continues a tradition of leading the market with content presented in a conversational student-oriented style. This text is designed to meet the needs of a wide spectrum of faculty - from the professor who just wants a good textbook and a few key supplements, to the professor who wants a top-notch fully integrated multimedia program.
Keywords: Marketing,Tiếp thị